2019
DOI: 10.17356/ieejsp.v5i1.483
|View full text |Cite
|
Sign up to set email alerts
|

Welfare Attitudes over time of V4-, Northern- and Western European countries in ESS Round 4 and Round 8 data

Abstract: Welfare Attitudes over time of V4-, Northern-and Western European countries in ESS Round 4 and Round 8 data  [piterova@saske.sk] (Institute of Social Sciences, CSPS SAS); [vyrost@saske.sk] (Institute of Social Sciences, CSPS SAS) Intersections.EEJSP 5(1): 143-162. AbstractWelfare attitudes are a complex and multidimensional phenomenon. Social solidarity in the sense of interdependence is understood as the first dimension of welfare attitudes, while differentiation -in terms of how people usually make a distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In the Nordic countries, however, the relative homogeneity in terms of high trust towards institutions and other people (Piterová and Vyrost, 2019) may have led to a less clear pattern of welfare support. Likewise, lower levels of inequality and less widespread poverty risks in these countries (Kulin and Svallfors, 2013) suggest higher levels of socio-economic homogeneity within their populations, which could also lead to fewer differences in welfare support between social groups.…”
Section: Resultsmentioning
confidence: 99%
“…In the Nordic countries, however, the relative homogeneity in terms of high trust towards institutions and other people (Piterová and Vyrost, 2019) may have led to a less clear pattern of welfare support. Likewise, lower levels of inequality and less widespread poverty risks in these countries (Kulin and Svallfors, 2013) suggest higher levels of socio-economic homogeneity within their populations, which could also lead to fewer differences in welfare support between social groups.…”
Section: Resultsmentioning
confidence: 99%
“…As a future research lead, considering the existing data is to assess the extent to which welfare attitudes in European countries are affected by contextual factors, such as the presence of crisis or pre-crisis (Piterová & Výrost, 2019). The ESS scale could also support longitudinal studies of cross-national data due to the increasing importance of this area (Davidov, 2008).…”
Section: Conclusion Limitations and Future Research Agendamentioning
confidence: 99%
“…Svallfors (2013) approached the concept of quality of government, confirming that the perceived quality of government and egalitarianism influenced attitudes to social spending and taxes. The research into types of welfare attitudes is still beginning and explores differences in interpersonal and institutional trust and values (Piterová & Výrost, 2019). Daniele and Geys (2015), within a similar approach, concluded that interpersonal trust has a positive relationship with welfare state support.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations